Development of Problem-solving Ability and Analytical Thinking Ability in Science Using Problem-based Learning on Natural Disasters of General Science Students - Laeid-on, Karupakorn; Promden, Worrawat; Lomarak, Tepporn; Sangsila, Arunrussamee; Innok, Niphon (Journal of Inclusive and Innovative Education, 2025)
This study aims to enhance problem-solving skills and analytical thinking through the implementation of problem-based learning (PBL) activities. The research sample comprises second-year students majoring in General Science at the Faculty of Education, Buriram Rajabhat University, during the first semester of the 2024 academic year. Participants were selected using a cluster random sampling technique. The research instruments consisted of problem-based learning lesson plans, a problem-solving ability test, a scientific analytical thinking test, and a questionnaire assessing students’ satisfaction with the learning experience. Data analysis was conducted using repeated measures analysis of variance (ANOVA) alongside descriptive statistical measures, including mean and standard deviation. The results indicate that students who engaged in problem-based learning exhibited a statistically significant improvement in problem-solving skills and scientific analytical thinking at the .05 significance level. Their problem-solving and analytical thinking abilities during and after the instructional intervention were significantly higher than those observed prior to participation. Furthermore, students reported a high level of satisfaction with the problem-based learning approach. Qualitative data obtained through interviews and classroom observations further revealed that students developed a positive attitude toward learning science, engaged in independent problem-solving, actively collaborated with peers, and effectively exchanged ideas.